Pengaruh Brand Ambassador Terhadap Keputusan Pembelian Produk Skintific Di Kota Bima - Husnul Hatimah; Sri Ernawati; Amirulmukminin Amirulmukminin (Universitas Riau Kepulauan, 2026)
The purpose of this study was to determine the influence of brand ambassadors on purchasing decisions for Skintific products in Bima City. This study was an associative study using a Likert scale questionnaire as the research instrument. The sample in this study was 90 respondents who had purchased and used Skintific products, both from Bima City and aged 18 years. Data were collected through observation, questionnaires, and literature studies. This study was analyzed using validity tests, reliability tests, simple regression analysis, correlation tests, determination tests, and t-tests. The results showed that there was a significant influence of brand ambassadors on purchasing decisions for Skintific products in Bima City.